Can short-term foreign exchange volatility be predicted by the Global Hazard Index? - Vincent Brousseau; Fabio Scacciavillani (European Central Bank (ECB), 2001)
This paper examines the predictive properties of risk indicators for the foreign exchange markets. In particular it considers the predictive properties of historical volatilities and implied volatilities for movements in various bilateral exchange rates and compares them with the analogous properties of a composite indicator of risk, the Global Hazard Index (GHI). The GHI is a function of the implied volatility derived from currency options on the three major exchange rates, i.e. the euro-US dollar, the US dollar-yen and the euro-yen. For the empirical analysis this paper employs the concept of kernel volatility, which, loosely speaking, expresses the volatility of one variable conditional on the level of another. Simple regressions show that the levels of all the indicators on a particular day have a strong link to the variance of the nominal bilateral exchange rate on the next day. A strong overall influence is displayed by the GHI, especially for the currencies of small open economies.
Keywords: F01; F31; 330